2018
DOI: 10.1016/j.neubiorev.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Basal ganglia and beyond: The interplay between motor and cognitive aspects in Parkinson’s disease rehabilitation

Abstract: Parkinson's disease (PD) is characterized by motor and cognitive dysfunctions, affecting the motor behaviour. We summarize evidence that the interplay between motor and cognitive approaches is crucial in PD rehabilitation. Rehabilitation is complementary to pharmacological therapy and effective in reducing the PD disturbances, probably acting by inducing neuroplastic effects. The motor behaviour results from a complex integration between cortical and subcortical areas, underlying the motor, cognitive and motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 183 publications
3
84
0
1
Order By: Relevance
“…There is growing evidence that physiotherapy interventions improve gait [13][14][15][16][17][18][19] and balance performance in PD [20][21][22][23][24][25][26][27][28]. Physiotherapy typically involves functional gait and balance exercises [9,10,24] that translate directly to daily life activities [29][30][31]. Moreover, compensation strategies such as rhythmic auditory cueing [32] have an immediate effect on walking speed, stride length and cadence [16,17,33].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that physiotherapy interventions improve gait [13][14][15][16][17][18][19] and balance performance in PD [20][21][22][23][24][25][26][27][28]. Physiotherapy typically involves functional gait and balance exercises [9,10,24] that translate directly to daily life activities [29][30][31]. Moreover, compensation strategies such as rhythmic auditory cueing [32] have an immediate effect on walking speed, stride length and cadence [16,17,33].…”
Section: Introductionmentioning
confidence: 99%
“…Participants demonstrated difficulties in conducting the task in a smooth manner ("flows"), persisting with actions in a coordinated manner, making motor adjustments ("calibrates", "coordinates", "adjusts") and altering performance speed to conform to task requirements ("times"). Reduced automatic internal responses to control, time and continue motor performance are well-known problems in PD and relate to dysfunction in the basal ganglia (5,25). To enhance movement, it is suggested that people with PD can use compensatory strategies that bypass the basal ganglia and tap into higher level attention strategies, sensory cueing and planning strategies (5,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…People with PD have difficulty performing habitual daily tasks, requiring them to use higher level thinking strategies to carry out daily activities that were previously automatic (4,5). At the same time, people with PD may experience cognitive deficits in executive functions, attention, processing speed, working memory and visuospatial functions (6).…”
mentioning
confidence: 99%
“…It is clear that the system participates in numerous non-motor functions that include motivational and emotional processing that involves integrating internal and external information (Berridge & Cromwell, 1990;Ferrazzoli et al, 2018;Salamone, Yohn, Lopez-Cruz, San Miguel, & Correa, 2016;Schneider & Lidsky, 1981). The pallidal region has medial (i.e., internal segment), lateral (i.e., external segment), and ventral subregions; and the substantia nigra contains two main subregions: the pars compacta and the pars reticulata.…”
Section: Ba Sal G Ang Lia Sys Tem: Fun C Ti On and Dys Fun C Tionmentioning
confidence: 99%
“…This set of BG structures comprises the largest subcortical system in the brain, and its complex connectivity and internal structure have made it extremely difficult to address questions about its functional nature. It is clear that the system participates in numerous non-motor functions that include motivational and emotional processing that involves integrating internal and external information (Berridge & Cromwell, 1990;Ferrazzoli et al, 2018;Salamone, Yohn, Lopez-Cruz, San Miguel, & Correa, 2016;Schneider & Lidsky, 1981).…”
Section: Ba Sal G Ang Lia Sys Tem: Fun C Ti On and Dys Fun C Tionmentioning
confidence: 99%